A new hydrazone-linked covalent organic framework for Fe(iii) detection by fluorescence and QCM technologies. Issue 19 (30th April 2021) - Li, Dian-Mei; Zhang, Shu-Yuan; Wan, Jia-Yi; Zhang, Wen-Qian; Yan, Yi-Lun; Tang, Xi-Hao; Zheng, Sheng-Run; Cai, Song-Liang; Zhang, Wei-Guang
Abstract : A new stable hydrazone-linked covalent organic framework was synthesized, which can be used as either a fluorescent probe or a COF-based QCM sensor for the identification of metal ions, showing high selectivity and sensitivity toward Fe(iii ) ions. Abstract : Since Fe(iii ) ions are of importance in biological systems, the development of new sensors for detecting Fe(iii ) with excellent selectivity and low detection limit is desirable. Herein, a new stable hydrazone-linked covalent organic framework (COF), namely, Tfpa–Mth COF, was synthesized by the Schiff-base condensation reaction between tris(4-formylphenyl) amine (Tfpa) and a chiral hydrazide precursor (Mth). The ethanol-dispersed Tfpa–Mth COF can be used as a fluorescence sensor for the detection of Fe(iii ) ions, showing high selectivity and low detection limit (64 nM). Moreover, a novel COF-based quartz crystal microbalance (QCM) sensor has been fabricated by the in situ growth of the Tfpa–Mth COF on an amino-modified QCM chip. Such a COF-based QCM sensor, with a uniform surface and thickness of the Tfpa–Mth COF film on the surface, is able to monitor Fe(iii ) ions in real-time with high selectivity. The recognition process, as a result of Fe(iii ) immobilization on the Tfpa–Mth COF framework, is further verified by zeta potential measurements and X-ray photoelectron spectroscopy. To the best of our knowledge, this represents the first report on the development of COF-based QCM sensors for metal ion detection. Exploration of the COF-based QCM sensor in our work demonstrates the new pathway for the selective detection of metal ions.